0.8-μW CMOS bulk-driven linear operational transconductance amplifier in 0.35-μm technology - Yodtean, Apiradee; Isarasena, Pasin; Thanachayanont, Apinunt (My University, 2010)
This paper proposes a low-voltage linear operational transconductance amplifier (OTA) in a 0.35-μm CMOS process. The proposed OTA employs a bulk-driven differential input stage with resistive source degeneration and the flipped-voltage follower topology to achieve high linearity under low power supply voltage. The proposed OTA dissipates 0.8 μW from a single 0.8-V power supply voltage. Simulation results with showed that a linear differential input voltage range of 470 mV was achieved with less than 1% total harmonic distortion. © 2010 IEEE.
Keywords: bulk-driven; flipped voltage follower; operational transconductance amplifier; source degeneration